The Pavagada Pediatric Eye Disease Study: Objectives, Methodology and Participant Characteristics. (30th April 2013) - Kemmanu, Vasudha; Hegde, Kaushik; Devagirkar, Smitha; Pujar, Chandrakant; Shetty, Bhujang K.; Kumaramanickavel, G.; McCarty, Catherine A.
ABSTRACT: Purpose : To explain the objectives and methodology of a population-based survey of children ≤15 years in rural South India. Methods : A population-based cross sectional survey was performed by trained field workers (1st phase). Children with eye disease were referred to the peripheral rural hospital (2nd phase) to be examined by a general ophthalmologist. If major eye disease (cataract, strabismus) was identified they were referred to a pediatric ophthalmologist (3rd phase). Results : The sample size was 29, 850. In the 1st phase, 23, 100 children were screened (response rate 77.39%). There were about 33% of children in each of the three stratified age groups (0–5, 6–10 and 11–15 years), with a nearly equal sex distribution in each group (range 47% to 52%). Of the 23, 100 screened, 1538 were referred to the peripheral rural hospital. The general ophthalmologist evaluated 647 patients (42%) who came to the peripheral rural hospital (2nd phase) and referred 59 children to the pediatric ophthalmologist (3rd phase). The pediatric ophthalmologist, in addition to evaluating the 59 children referred from the 2nd phase, also evaluated those who did not report (891/1538) to the peripheral rural hospital. This evaluation was done in the field itself. All the 1538 children referred by the field workers were thus seen by an ophthalmologist (647 by the general ophthalmologist, 891 by the pediatric ophthalmologist and 59 by both). Conclusion : The study is expected to provide information about the prevalence of pediatric ocular morbidity that could help plan intervention strategies in this area.